Probiotic Characteristics of Lactiplantibacillus plantarum CECT 9435 and Its Survival and Competitive Properties Under Simulated Conditions of the Child Gut Microbiota - Teresa Requena; M. Carmen Martínez-Cuesta; Rosa Aznar; M. Luz Mohedano; Paloma López; Patricia Ruas-Madiedo (Probiotics and Antimicrobial Proteins, 2025)
Probiotics are valuable microorganisms effective in reducing malnutrition-related infections in children. In this work, a collection of lactobacilli strains representative of traditional Andean fermented beverages was in vitro screened for their capability to survive the gastrointestinal transit, to adhere to the intestinal epithelium and to compete under simulated conditions of the child gut microbiota. The results allowed the selection of the riboflavin overproducing strain Lactiplantibacillus plantarum CECT 9435 based on its good rate of survival under in vitro gastrointestinal conditions when included in a food matrix representing the fortified food supplement Incaparina. The strain also showed good adhesion to HT29 cells producing mucus and outstanding performance in E. coli competition for the adhesion to this epithelial cell line. L. plantarum CECT 9435 gut performance was also evaluated in the child intestinal microbiota simulated in a dynamic gut model (BFBL simulator). The viability of the probiotic candidate in the gut conditions was high during the 7-day intervention period, reaching over 1 × 10 7 counts in each of the reactors simulating the three colonic regions. The transient viability of L. plantarum CECT 9435 within the child gut microbiota and its adhesion capacity to intestinal cells could facilitate the strain potential benefits as probiotic added to fortified supplementary foods destined to malnourished children.